2017
DOI: 10.3171/2017.3.spine1622
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous hemangioblastoma of the cervical spine: case report

Abstract: A 69-year-old woman presented with bilateral upper-extremity radiculopathy and neck pain after a mechanical fall. Admission CT and MRI of the cervical spine demonstrated a pathological C-4 fracture. Subsequent malignancy workup was negative. A CT-guided biopsy of the lesion showed intraosseous hemangioblastoma. Hemangioblastoma is a highly vascular, slow-growing tumor of the CNS; intraosseous location of this tumor is extremely rare. The authors review the diversity of its presentation and the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…T here are only a few case reports (20 cases) on "intraosseous" cervical tumors, such as hemangioblastomas, malignant peripheral nerve sheath tumors, and schwannoma [3][4][5][6][7] . Although a few studies have reported IONF occurring in the mandible, humerus, and clavicle [8][9][10] , there is only 1 case (from 1960) of IONF reported in the cervical spine 11 .…”
Section: Discussionmentioning
confidence: 99%
“…T here are only a few case reports (20 cases) on "intraosseous" cervical tumors, such as hemangioblastomas, malignant peripheral nerve sheath tumors, and schwannoma [3][4][5][6][7] . Although a few studies have reported IONF occurring in the mandible, humerus, and clavicle [8][9][10] , there is only 1 case (from 1960) of IONF reported in the cervical spine 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic HBs are often isolated cases, rarely recur following a complete surgical resection, and are associated with a more severe neurological deficits. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Hemangioblastomas are vascular neoplasms that account for 1%–3% of all central nervous system (CNS) tumors and are usually present in the cerebellum, brainstem, or spinal cord. 1–4 Although the majority of spinal hemangioblastomas are located in the cervical and thoracic regions, 1 , 5–13 they have also been reported in the lumbar and sacral spine, 5 cauda equina, 2 , 14 , 15 and filum terminale. 16 , 17 Few cases have been described in 18–24 or at the level of 25–27 the conus medullaris.…”
mentioning
confidence: 99%
“… 2 , 7 , 28 , 29 A total of 70%–80% of spinal cord lesions arise sporadically, whereas the remainder are associated with von Hippel-Lindau syndrome. 1 , 3 , 11 , 30 von Hippel-Lindau syndrome is a tumor suppressor gene syndrome marked by mutations in the VHL gene in the chromosome 3p25–26 region. 10 , 30 It is transmitted in an autosomal dominant manner and is associated with several pathological conditions, including CNS tumors (hemangioblastomas, retinal angiomatosis, endolymphatic sac tumors), renal cell carcinoma/cysts, pancreatic carcinomas/cysts, pheochromocytomas, and epididymal cystadenomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation